Detection of IgM antibodies against bovine viral diarrhea virus using IgM capture ELISA on farms with persistently infected cattle - Kiyohiko Andoh; Takumi Hayashi; Asami Nishimori; Yuichi Matsuura (Heliyon, 2024)
Bovine viral diarrhea (BVD) is a serious disease in cattle and causes economic losses in the livestock industry. Bovine viral diarrhea virus (BVDV) is the causative agent of BVD and spreads among herds via persistently infected (PI) animals that shed large amounts of the virus throughout their lives. Hence, identifying, and culling PI animals and assessing the immune status against BVDV on farms are important strategies for controlling BVD. Additionally, estimating the time when individuals around PI animals were infected with the virus could also be supportive information to interpret a farm status. We herein constructed a BVDV-specific IgM capture ELISA using recombinant E2 antigen and applied it to detecting BVDV-specific IgM antibodies on farms with identified PI cattle. The IgM ELISA detected anti-BVDV IgM antibodies during approximately 2–3 weeks post infection and identified IgM-positive cattle on two farms with recognized PI cattle. Virus neutralization tests showed that almost all adult cattle had high virus neutralization antibodies against BVDV, and sero-positive and -negative cattle coexisted in young herds. In this situation, most of the IgM-positive cattle were in relatively young animals, implying that BVDV had been recently spreading in these young herds. Thus, our findings demonstrated that detecting IgM antibodies could be useful to know recent BVDV infection on farm on which PI cattle were identified.